The polotical economy of hunger : selected essays - Sen, Amartya, ed.; Hussain, Athar, ed. (New Delhi : Oxford University Press, 1999)
Economics
Keywords: Political economy; Hunger; Food; Famine prevention; Independent press; Public policy; Basic needs; Food problems; Poverty